Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1959
DOI: 10.1146/annurev.ph.21.030159.001151
|View full text |Cite
|
Sign up to set email alerts
|

Digestive System

H W Davenport

Abstract: To understand digestion we need first a gross, qualitative description of the fate of ingesta; what is secreted in response to the meal, how ingesta are transformed by reaction with secretions and by the propulsive mechanism, what is absorbed and what rejected. This should be followed by an exact quantitative and temporal description in the style of chemical kinetics in which net changes are reported in terms of two-way fluxes. Coupled with this should be a detailed account of the physiological and morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1964
1964
1964
1964

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 92 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…Since the tissues do not contain an enzyme for utilizing either lactose or sucrose, both of these disaccharides if absorbed as such are excreted in the urine (Hawk et al, 195^-; Davenport, 1959)o Wallace et al (1951) reported an apparent digestion coefficient of 93^ for sucrose in a ration which contained 32^ sucrose and 50^ dried skimailk. However, Ruber et al» (1958) found that only 57^ of the sucrose was digested in a diet containing 0.7 g sucrose per pound of body weight per feeding.…”
Section: Sucrose In Growth and Digestion Studiesmentioning
confidence: 99%
“…Since the tissues do not contain an enzyme for utilizing either lactose or sucrose, both of these disaccharides if absorbed as such are excreted in the urine (Hawk et al, 195^-; Davenport, 1959)o Wallace et al (1951) reported an apparent digestion coefficient of 93^ for sucrose in a ration which contained 32^ sucrose and 50^ dried skimailk. However, Ruber et al» (1958) found that only 57^ of the sucrose was digested in a diet containing 0.7 g sucrose per pound of body weight per feeding.…”
Section: Sucrose In Growth and Digestion Studiesmentioning
confidence: 99%